Toe flexor muscle strength and morphological characteristics of the foot in judo athletes - Koyama, K.; Hirokawa, M.; Yoshitaka, Y.; Yamauchi, J. (International Journal of Sports Medicine, 2019)
Whether practicing in judo influences the muscle strength and morphological characteristics of the foot is unknown. The purpose of this study was to determine the toe flexor muscle strength and morphological characteristics of the foot in judo athletes. Judo athletes (JUDO, men=24) and age-, gender- and body mass-matched physically active healthy subjects (CON, men=24) were recruited, and their toe flexor strength and morphological characteristics of the foot were compared. The maximum isometric toe flexor strength and foot intrinsic muscle thicknesses were measured using a toe grip dynamometer and a B-mode ultrasound, respectively. Foot arch height was assessed as the distance between the navicular tuberosity of the foot and the floor in the sitting and standing positions. JUDO showed a significantly lower foot arch height and smaller foot arch index than CON, whereas foot length and muscle thickness did not significantly differ between groups. The toe flexor strength relative to total muscle thickness was significantly larger in JUDO than CON. The foot arch dynamics was significantly larger in JUDO than CON. This study suggests that exercise training specific to judo may affect the force-generating capacity, morphological structure and arch function of the foot.